The impact of social servicescape factors on customers' satisfaction and repurchase intentions in mid-range restaurants in Baltic States - Mangirdas Morkunas; Elzė Rudienė (Journal of Open Innovation: Technology, Market, and Complexity, 2020)
The present paper studies the importance of social servicescape factors to customer satisfaction in middle-priced restaurant services. This paper fills the existing literature gap on the importance of social servicescape factors onto customers' satisfaction in middle-priced services. A survey of 514 respondents from three capitals of the Baltic States was conducted for the purpose of the present study. Descriptive statistics together with an independent samples t-test and partial least squares path analysis were employed for data processing. The results obtained confirmed the hypothesis about the importance of social servicescape attributes to customer satisfaction. The study also highlighted the difference in gender attitudes towards intangible aspects of service delivery. The research confirmed the existence of a relationship between customer satisfaction and repurchase intentions, although to a lesser extent than could have been anticipated from the literature review. The findings of the study covered by the present paper allow us to position middle-priced restaurants closer to luxury ones compared to casual restaurants.
Keywords: 650; social servicescape; customer satisfaction; repurchase; restaurants; Baltic States